A Colorful Question Game to Improve Children Motor Skills in 4th Class Elementary School - Selvi Atesya Kesumawati; Aprizal Fikri; Noviria Sukmawati; Husni Fahritsani (UNIB Press, 2023)
This research aims to develop a basic motor skills learning model through game activities tailored to the developmental stages of students' ages. The game model used in this research is called